Patterns of Species Richness, Range Size, and Their Environmental Correlates for South American Anurans - Vasconcelos, Tiago S. [UNESP]; Silva, Fernando R. da; Santos, Tiago G. dos; Prado, Vitor H. M.; Provete, Diogo B.; Vasconcelos, TS; DaSilva, FR; DosSantos, TG; Prado, VHM; Provete, DB (Springer, 2019)
Species richness and range size gradients have been correlated with environmental conditions at broad spatial scales, yet these effects are commonly context-dependent for different geographical regions. Here we assembled range maps of South American anurans and used spatial and nonspatial regressions to assess the potential influences of environmental variables on the gradients of species richness and range sizes. Additionally, we evaluated the consistency of these environmental drivers separately for temperate/subtropical and tropical regions of South America. We found that vegetation structure, temperature, and energy-water balance were the strongest predictors of species richness at the continental scale; temperature, productivity, and elevation were the best predictors for range size. Explanatory power of predictors shifted across different regions of the continent: in the tropical, vegetation structure was the strongest correlate of species richness, and in the temperate/subtropical, temperature and energy-water balance were the most important predictors. As for range size, elevation and temperature were the best predictors in the tropical region, whereas temperature seasonality was the strongest predictor in the temperate/subtropical region. Our results support the idea that different environmental filters can vary according to the latitude, reinforcing the relevance of evaluating patterns at multiple spatial scales to understand environmental drivers of biodiversity.
Keywords: Amphibians; Climate variability; Energy water; Environmental gradients; Range size; Species diversity; Non stationarity; Autoregressive models; Hierarchical partitioning